2011
DOI: 10.1109/tbme.2011.2107322
|View full text |Cite
|
Sign up to set email alerts
|

Bubbly Cavitating Flow Generation and Investigation of Its Erosional Nature for Biomedical Applications

Abstract: The paper presents a study of the generation of hydrodynamic bubbly cavitation in microchannels to investigate the destructive energy output resulting from this phenomenon and its potential use in biomedical applications. The research performed in this study includes the experimental results from bubbly cavitation experiments and the findings showing the destructive effects of bubbly cavitating flow on selected specimens and cells. The bubbles caused by hydrodynamic cavitation are highly destructive at the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…However, applications of HC at the conventional scale have been successfully realized in the food and beverage industry [4][5][6] and hydrometallurgy 7 . Furthermore, its extensive applications at the microscale are emerging, such as wastewater treatment 8 , biomedical applications [9][10][11] , energy harvesting 12,13 , and liquid phase exfoliation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, applications of HC at the conventional scale have been successfully realized in the food and beverage industry [4][5][6] and hydrometallurgy 7 . Furthermore, its extensive applications at the microscale are emerging, such as wastewater treatment 8 , biomedical applications [9][10][11] , energy harvesting 12,13 , and liquid phase exfoliation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Kosar et al found that hydrodynamic-responsive NBs could induce damage on leukemia/lymphoma cells, kill prostate cells, and ablate benign prostatic hyperplasia tissue. 294,295 The same group also demonstrated the potential of these collapsible bubbles for use in kidney stone treatment in vitro and found that they could successfully erode stones with an erosion rate of 0.31 mg/min. 296 Subsequently, they also developed a biomedical device prototype responsive NBs are limited.…”
Section: Delivery Of Therapeutic Gasesmentioning
confidence: 97%
“…Our experimental set-up was as previously described. 26 A schematic presentation of the experimental set-up is shown in Figure 1. Briefly, a pressure driven flow through a 0.5 cm long polyether ether ketone (PEEK) probe with an inner diameter of 147 mm, was used as a flow restrictive orifice leading to low local pressures and generation of hydrodynamic bubble cavitation.…”
Section: Experimental Set-up For Hydrodynamic Bubble Cavitation Generationmentioning
confidence: 99%
“…We have previously shown that hydrodynamic cavitation could kill leukemia cells in suspension culture and erode calcium oxalate kidney stones. 26,27 In this work, we tested the efficacy of hydrodynamic cavitation in killing prostate cells in culture and its potential to ablate BPH tissues. The molecular mechanisms of the destructive effects of hydrodynamic cavitation were also analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%